QORAQALPOG‘ISTON FLORASINING NAFAS OLISh TIZIMI KASALLIKLARIDA QO‘LLANILADIGAN AYRIM DORIVOR TURLARI - Eshmuratov, R.A.; Turdimuratova, U. (SCIENCE and SOCIETY, 2025)
This article covers more than 70 species of medicinal plants of the flora of Karakalpakstan used to treat respiratory diseases, the organs used, their chemical composition, and the area of application in treatment. The obtained data are important for the scientific substantiation of folk medicine, as well as for the development of new phytotherapeutic preparations.
Keywords: flora of Karakalpakstan; medicinal plants; respiratory diseases; folk medicine; plant organs; chemical composition